Stress analysis in a half plane elasticity. - Nik Long, Nik Mohd Asri; Eshkuratov, Zainidin K.; Yaghobifar, Mohammad (CESER Publications, 2011)
The biharmonic equation which governs the stress problem in a half plane elasticity is solved for the stresses using the Fourier transform technique. The Fourier transformed pressure exerted on a half plane is written into the basis of even and odd terms. It is found that the stresses at every point in a half plane elasticity are decomposable into some obtainable functions. An example is given to show the efficiency of the proposed technique.